1981
DOI: 10.1177/1077727x8101000211
|View full text |Cite
|
Sign up to set email alerts
|

Clothing Demand in the United States: A Cross‐Sectional Analysis

Abstract: This paper examined factors influencing clothing expenditures by households in the United States. In particular, the impact of various household characteristics on clothing expenditures was investigated using data from the 1972–73 Bureau of Labor Statistics Consumer Ex penditure Survey. The results indicated that income plays a major role in concert with demographic characteristics in determining household expenditures on clothing and services. Expenditures were positively related to income and education and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
120
3
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(131 citation statements)
references
References 5 publications
7
120
3
1
Order By: Relevance
“…Given the reliance of these studies on economic theory for a theoretical framework, some measure of income is typically included. As economic theory predicts, empirical support for a positive relationship between income (or total expenditures) and apparel expenditures was found (Dardis et al, 1981;DeWeese, 1993;DeWeese and Norton, 1991;Douthitt and Fedyk, 1988;Nelson, 1989;Norum, 1989Norum, ,1992Wagner and Hanna, 1983;Zhang and Norton, 1995). Total consumption expenditures, used in several studies to proxy income (Dardis et aL, 1981;Nelson, 1989;Wagner and Hanna, 1983), provide a better fit in models built for prediction purposes (Dardis et al, 1981).…”
Section: Previous Researchmentioning
confidence: 96%
See 2 more Smart Citations
“…Given the reliance of these studies on economic theory for a theoretical framework, some measure of income is typically included. As economic theory predicts, empirical support for a positive relationship between income (or total expenditures) and apparel expenditures was found (Dardis et al, 1981;DeWeese, 1993;DeWeese and Norton, 1991;Douthitt and Fedyk, 1988;Nelson, 1989;Norum, 1989Norum, ,1992Wagner and Hanna, 1983;Zhang and Norton, 1995). Total consumption expenditures, used in several studies to proxy income (Dardis et aL, 1981;Nelson, 1989;Wagner and Hanna, 1983), provide a better fit in models built for prediction purposes (Dardis et al, 1981).…”
Section: Previous Researchmentioning
confidence: 96%
“…During the past fifteen years, US clothing demand has received iucreasmg attention from academic researchers (Dardis et al, 1981;DeWeese, 1993;DeWeese and Norton, 1991;Nelson, 1989;Norum, 1989Norum, ,1992Wagner and Hanna, 1983;Zhang and Norton, 1995), Researchers measured income elasticities, explored the effect of family life cycle and composition, and analyzed the role of labor participation in clothing demand. Region, although included in many of the analyses, was not a primary focus of any of the studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…우리나라 가계의 중요한 소비재의 하나인 의류에 대한 수요탄력 성은 가계의 의류소비패턴을 밝히는 중요한 분석지표 임에도 불구하고 가계소비재에 대한 수요분석은 주로 식품에 대한 수요탄력성을 추정하는 것 (Kim & Sakong, 1994;Lee & Choi, 1999;Yoon et al, 2003) (Dardis et al, 1981). (Eastwood, 1984;Philips, 1983).…”
Section: 의류수요에 대한 선행연구unclassified
“…Using data from the 1972-73 Consumer Expenditure Survey, Dardis, Derrick, and Lehfeld (1981) tested the determinants of clothing expenditure. They found that clothing expenditure was pos itively related to income, education, and family size.…”
Section: Previous Researchmentioning
confidence: 99%